Penerapan Intervensi Terapi Qur’anic Healing pada Klien Tn. S dengan Gangguan Persepsi Sensori: Halusinasi Pendengaran - Amanda Virga Pratidina; Setiyo Adi Nugroho; Maulidiyah Junnatul Azizah Heru (Universitas Pahlawan Tuanku Tambusai, 2024)
One of the mental health problems is hallucination patients. Hallucinations can cause sensory perception disorders that are false or do not occur in reality, characterised by changes in sensory perception of perception, feeling false sensations in the form of sound, sight, taste, touch, or smell. About 70% of hallucinations patients experienced by people with a mental health condition are auditory hallucinations. One of the therapies that can be used for handling auditory hallucination patients is Qur'anic Healing therapy. Purpose: This study aims to Identify the Application of Qur'anic Healing Therapy Interventions to Mr. S's Clients with Sensory Perception Disorders: Auditory Hallucinations. Methods: Data collection techniques using interviews, observation, physical examination and documentation, the implementation of qur'anic healing therapy for 15-30 minutes to control auditory hallucinations. Results: Data analysis shows that the nursing diagnosis is sensory perception disorder. Giving qur'anic healing therapy is one of the interventions that can be applied to control hallucinations. Conclusion: Based on the evaluation results obtained from nursing care, qur'anic healing therapy can control auditory hallucinations.